Habitual snoring and primary enuresis in children - Muhammad Adib Mahara; Oke Rina Ramayani; Elmeida Effendy; Munar Lubis; Rosmayanti Siregar; Beatrix Siregar; Rafita Ramayanti (Paediatrica Indonesiana, 2018)
Background Obstructive sleep-disordered breathing is assumed to be associated with primary enuresis in children. Prolonged enuresis may cause developmental and emotional disorders, as well as poor school performance. Objective To determine the relationship between habitual snoring and primary enuresis in children. Methods A cross-sectional study was conducted in Muara Batang Gadis District, North Sumatera in April 2016. Subjects were children aged 5-14 years. The Sleep Disturbance Scale for Children (SDSC) questionnaire was used to measure the symptoms of sleep disordered breathing; the International Association Child and Adolescent Psychiatry and Allied Professions (IACAPAP) questionnaire was used to assess for the presence of primary enuresis. The questionnaires were answered by the children’s parents. Data were analyzed using Chi-square and logistic regression tests. A P value of <0.05 was considered to be statistically significant. Results The mean age of 110 participants was 9.23 (SD 2.16) years. Twenty-seven (24.5%) subjects snored more than three nights per week (habitual snorers) and 18 (16.4%) subjects had primary enuresis. There was a significantly higher percentage of habitual snorers with enuresis than that of snorers without enuresis (55.5% vs. 18.4%, respectively) (P<0.05). Conclusion There is a significant relationship between habitual snoring and primary enuresis.